Efficacy and safety of neoadjuvant chemoimmunotherapy and chemotherapy in patients with potentially resectable stage IIIA/IIIB NSCLC: a retrospective study - Wang, Yuchen; Ma, Xiaobo; Ma, Kewei; Chen, Xi; He, Hua; Zhao, Xiangye; Fan, Mengge; Xu, Yinghui (Frontiers in Immunology, 2025)
BackgroundTreatment of locally advanced unresectable non-small cell lung cancer (NSCLC) is a significant challenge, especially for patients with IIIA/IIIB NSCLC. Patients receiving neoadjuvant chemoimmunotherapy (NCI) show improved pathological responses and disease-free survival (DFS) compared to those receiving Neoadjuvant chemotherapy (NC). However, there is still no consensus on the treatment for potentially resectable stage IIIA/IIIB NSCLC.MethodsThis retrospective study included 71 patients newly diagnosed with stage III NSCLC at our institution between 2017 and 2023: 46 patients received NCI and 25 patients received NC followed by surgical resection. Their clinicopathological characteristics were reviewed and analyzed.ResultsPatients who received NCI had a significantly longer DFS. The median DFS was 15 months in the NC group (hazard ratio: 0.186, 95% confidence interval[CI]: 0.073–0.479; P<0.001) but had not been reached in the NCI group. The percentage of patients achieving a major pathologic response was 65.9% (29/44, 95% CI: 50.0%–79.1%) with NCI and 16.7% (4/24, 95% CI: 5.5%–38.2%) with NC alone(P<0.001). The percentage of patients with pathologic complete response was 36.4% (16/44, 95% CI: 22.8%–52.3%) after NCI compared with 8.3% (2/24, 95% CI: 1.5%–28.5%) after NC (P = 0.012). The survival curve shows that the overall survival for the NCI group has a better trend than that of the NC group, but there is no significant difference (P=0.193). The incidence of all-grade adverse events was greater in the NCI group than in the NC group (80.4% vs. 64.0%). The incidence of grade ≥3 adverse events was 10.9% (n=5) and 8.0% (n=2), respectively; however, these differences were insignificant.ConclusionsNCI is more effective and safer for patients with potentially resectable stage IIIA/IIIB NSCLC. Compared with NC alone, NCI significantly improves the pathological response and DFS without increasing adverse events.